Citizenship Education in Elementary Schools: Factors Influencing Classroom Participations of College Students - Liantori, Beni; Sujarwo, Sujarwo (FKIP Universitas Lampung, 2023)
Citizenship Education in Elementary Schools: Factors Influencing Classroom Participation of College Students. Objective: this reseach aims to analyze the factors that influence the lack of participation of college students in citizenship education in elementary schools. Method: a descriptive quantitative approach applied in this research with 125 pre-service elementary school teachers at Universitas Sarjanawiyata Tamansiswa as participants. Data collection uses questionnaires and interviews. This research uses data validity and reliability using triangulation. Data analysis uses the Miles and Huberman model. Findings: among five factors influencing students’ classroom participation, motivation had the highest score causing the decline in student activity in citizenship education in elementary school (70.1%), followed by lecturers’ roles in the classroom (66.7%) as the trigger for the decline in student activity. Furthermore, 56.5% of student conditions, 51.2% of learning environment and 50.6% of student anxiety. Conclusion: there are five factors identified as the root causes of low student activity in citizenship education in elementary school including student anxiety, the learning environment, the role of the lecturer in the classroom, and the student's condition. Keywords: classroom participation, citizenship education in elementary school, college students.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202338